2015
DOI: 10.1016/j.ejrnm.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Positive remodeling index by MSCT coronary angiography: A prognostic factor for early detection of plaque rupture and vulnerability

Abstract: KEYWORDSRemodeling index (RI); Coronary artery disease (CAD); Left anterior descending (LAD); Right coronary artery (RCA); Left circumflex artery (LCX) Abstract Purpose: To emphasis the role of MSCT utilizing the remodeling index in assessment of positive coronary remodeling which was associated with plaque rupture and vulnerability. Methods and material: Studied group included 35 patients with positive coronary remodeling. One lesion per patient was assessed, either a solitary lesion or the most significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…The percent stenosis, which is a ratio of the minimal lumen diameter at the site of the plaque to the mean of proximal and distal reference vessel diameters, did not correlate with coronary plaque area in coronary atherosclerotic lesions [ 27 ]. In contrast, the remodeling index, which is the ratio of the vessel diameter at the site of the plaque divided by the mean of the proximal and distal reference vessel diameters, strongly correlated with coronary plaque size in coronary atherosclerotic lesions [ 28 , 29 ]. In the present study, evolocumab increased the CT density and reduced the remodeling index of vulnerable coronary plaques.…”
Section: Discussionmentioning
confidence: 99%
“…The percent stenosis, which is a ratio of the minimal lumen diameter at the site of the plaque to the mean of proximal and distal reference vessel diameters, did not correlate with coronary plaque area in coronary atherosclerotic lesions [ 27 ]. In contrast, the remodeling index, which is the ratio of the vessel diameter at the site of the plaque divided by the mean of the proximal and distal reference vessel diameters, strongly correlated with coronary plaque size in coronary atherosclerotic lesions [ 28 , 29 ]. In the present study, evolocumab increased the CT density and reduced the remodeling index of vulnerable coronary plaques.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease is defined as clinically significant when luminal narrowing is present, typically at the 50% diameter reduction threshold. However, in early atherosclerosis, the first arterial changes consisted of compensatory enlargement of both the outer wall of the vessel as well as the lumen, termed compensatory enlargement or positive remodeling [7].…”
Section: Discussionmentioning
confidence: 99%
“…The data of correlation of remodeling index with demographic and risk factors were variable; Burke et al [15] found that positive remodeling was more in men and older group but Abdeldayem et al [7] found that no correlation was noted between either age, sex, and coronary risk factors with remodeling index, but the latter result can be explained by the small number of the study population (35 patients) and so less prevalence of risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Positive remodelling (expansion) of early lesions maintains lumen size despite plaque accumulation. 5 This explains why these lesions might pass undetected by conventional angiography. Coronary artery plaques with positive remodelling have a higher lipid content and macrophage count, both markers of plaque vulnerability.…”
Section: Introductionmentioning
confidence: 99%